CONCEPTUAL FRAMEWORK OF CONCEPTUAL PROBLEM BASED LEARNING MODEL TO FACILITATE CRITICAL THINKING SKILLS OF SENIOR HIGH SCHOOL STUDENTS - I Wayan Karmana; Taufik Samsuri (Faculty of Education and Teacher Training, UIN (State Islamic University) Syarif Hidayatul, 2018)
KERANGKA KONSEPTUAL MODEL CONCEPTUAL PROBLEM BASED LEARNING UNTUK MELATIHKAN KEMAMPUAN BERPIKIR KRITIS SISWA SEKOLAH MENENGAHAbstractLearning to facilitate critical thinking requires a set of specific learning models that aims to trains critical thinking skills that in this study is the development of conceptual problem based learning model. This study aims to develop a conceptual problem-based learning model to facilitate high school students’ critical thinking skills. This study is a development research that will produce a model of learning products, namely a valid Conceptual Problem Based Learning Model to facilitate high school students’ critical thinking skills. Validation of CPBL learning model includes two components namely content validity and construct validity. The result of data analysis shows that the CPBL model can be declared valid with reliability percentage of 97% (reliable) based on syntax model assessment that is: 1) prior knowledge; 2) organize; 3) investigate; 4) analyze; 5) evaluate; to facilitate critical thinking skills.AbstrakPembelajaran untuk melatihkan berpikir kritis memerlukan satu set model pembelajaran yang spesifik melatihkan kemampuan berpikir kritis yang dalam penelitian ini pengembangan model conceptual problem based learning. Penelitian ini bertujuan untuk mengembangkan model conceptual problem based learning untuk melatihkan kemampuan berpikir kritis siswa sekolah menengah. Penelitian ini merupakan penelitian pengembangan yang akan menghasilkan produk model pembelajaran, yaitu Model Conceptual Problem Based Learning yang valid untuk melatihkan kemampuan berpikir kritis siswa sekolah menengah. Validasi model pembelajaran CPBL meliputi dua komponen yaitu validitas isi (content validity) dan validitas konstruk (construct validity). Hasil analisis data menunjukkan bahwa model CPBL dapat dinyatakan valid dengan persentase reliabilitas sebesar 97% (reliabel) berdasarkan penilaian sintaks model yaitu: 1) prior knowledge; 2) organize; 3) investigate; 4) analyze; 5) evaluate; untuk melatihkan kemampuan berpikir kritis siswa sekolah menengah.